Political Law of Presidential Regulation Number 63 of 2019 on Trademarks - arief, sofyan; Herwastoeti; Umi Sakdiyah Rahmawati (Indonesia Law Reform Journal, 2022)
This article discusses trademarks in a legal political perspective. The existence of Presidential Regulation No. 63 of 2019 concerning the Use of Indonesian which regulates the use of Indonesian that must be used on trademarks owned by Indonesian citizens or Indonesian legal entities has conflicts with the Law Number 20 of 2016 On Trademarks and Geographical Indications, regarding the function and purpose of the Trademarks, so it is interesting to conduct discussions through normative juridical methods. The results of this study show that the principle of Lex Superior Derogat Lex Inferiori law, which is a principle that interprets higher legal norms, can be used as one of the tools in solving problems.  Thus, the position of Presidential Regulation Number 63 of 2019, is no more binding than the position and binding power of Law Number 20 of 2016 on Trademarks and Geographical Indications. Abstrak Artikel ini membahas merek dagang dalam perspektif politik hukum. Keberadaan Peraturan Presiden Nomor 63 Tahun 2019 tentang Penggunaan Bahasa Indonesia yang mengatur penggunaan bahasa Indonesia yang harus digunakan pada merek dagang milik warga negara Indonesia atau badan hukum Indonesia bertentangan dengan Undang-Undang Nomor 20 Tahun 2016 tentang Merek Dagang dan Indikasi Geografis, mengenai fungsi dan tujuan Merek Dagang,  sehingga menarik untuk melakukan diskusi melalui metode yuridis normatif. Hasil penelitian ini menunjukkan bahwa prinsip hukum Lex Superior Derogat Lex Inferiori, yang merupakan prinsip yang menafsirkan norma hukum yang lebih tinggi, dapat digunakan sebagai salah satu alat dalam memecahkan masalah.  Hal ini berimplikasi kedudukan Peraturan Presiden Nomor 63 Tahun 2019, tidak lebih mengikat dengan kedudukan dan daya mengikat Undang-Undang Nomor 20 Tahun 2016 Tentang Merek Dagang dan Indikasi Geografis.